Associations of smoking with cardiometabolic profile and renal function in a Romanian population-based sample from the PREDATORR cross-sectional study. (2nd October 2017) - Popa, Simona Georgiana; Moţa, Maria; Mihălţan, Florin Dumitru; Popa, Adina; Munteanu, Ioana; Moţa, Eugen; Serafinceanu, Cristian; Guja, Cristian; Hâncu, Nicolae; Catrinoiu, Doina; Lichiardopol, Radu; Bala, Cornelia; et al.
Abstract: Background: The impact of smoking on morbidity is well known, but in Romania, limited data are available regarding the smoking prevalence and relationship with cardiometabolic profile and kidney function. Objectives: To assess the association of smoking with cardiometabolic traits and kidney function, in a Romanian population-based sample from the PREDATORR study. Methods: PREDATORR was an epidemiological cross-sectional study. Between 2012 and 2014, participants were randomly selected from the lists of general practitioners and enrolled if they were aged 20 to 79 years, born and living in the past 10 years in Romania. Sociodemographic and lifestyle characteristics were collected through interviewer-administered questionnaires. Results: Overall, 2704 participants were included in the analysis, 18% of them being current smokers and 30.8% former smokers. Current smokers compared to non-smokers had higher total cholesterol (220.6 ± 50.4 versus 213.9 ± 86.8 mg/dl, P  = 0.017), LDL-cholesterol (137.8 ± 45.2 versus 130.7 ± 83.7 mg/dl, P  = 0.004) and glomerular filtration rate (96.9 ± 16.8 versus 90.7 ± 19.1 ml/min/1.73 m 2, P  <0.001) in women and higher triglycerides (170.7 ± 129.8 versus 144.3 ± 94.2 mg/dl, P  = 0.007), glomerular filtration rate (97.6 ± 17 versus 90.3 ± 18 ml/min/1.73 m 2, P  < 0.001) and lower HDL-cholesterol (48 ± 15.5 versus 50.4 ± 14.1 mg/dl, P  = 0.002) in men. Active smoking was associated with hypercholesterolaemia [OR: 1.40 (95% CI: 1.01–1.96), P  = 0.04] and low HDL-cholesterolaemia [OR: 1.39 (95% CI: 1.01–1.91), P  = 0.04] and negatively associated with overweight/obesity [OR: 0.67 (95% CI: 0.48–0.94), P  = 0.02]. Male former smokers had higher prevalence of abdominal obesity (82.4% versus 76.4%, P  = 0.02), hypertriglyceridaemia (43.6% versus 35.6%, P  = 0.01), hypertension (64% versus 56.4%, P  = 0.01) and ischaemic vascular disease (40.5% versus 30.9%, P  = 0.003) than male non-smokers. Conclusion: The PREDATORR study showed a high prevalence of smoking in the adult Romanian population providing data on the association of smoking with cardiometabolic traits.